An econometric analysis of the link between biodiesel demand and Malaysian palm oil market. - Applanaidu, Shri Dewi; Mohamed Arshad, Fatimah; Shamsudin, Mad Nasir; Abdel Hameed, Amna Awad (Canadian Center of Science and Education (CCSE), 2011)
The objective of this study is to describe the important factors affecting Malaysian palm oil industry especially biodiesel demand. To that end a market model representing palm oil production, import, world excess demand, domestic consumption, export demand, rest of the world excess supply and palm oil prices is formulated. A system of equations of eight structural equations and four identities is estimated by two stage least squares method using annual data for the period 1976-2008. The domestic price equation is formed to investigate the link between biodiesel demand and the Malaysian palm oil market. The domestic price is significantly affected by Malaysian ending stock, world palm oil price, biodiesel demand and lagged domestic price. The elasticity of Malaysian palm oil domestic price with respect to biodiesel demand is then obtained. Results suggest that biodiesel demand has a positive impact on the Malaysian palm oil domestic price. Thus, significant growth in biodiesel demand is important in explaining Malaysian palm oil price determination.